The Devine Doughnut Shop - Brown, Carolyn, 1948- (Montlake, 2023)
"For Grace Dalton, her sister, Sarah, and her cousin Macy, the Devine Doughnut Shop is a sweet family legacy and a landmark in their Texas town. As the fourth generation to run the Double D, they keep their great-grandmother's recipe secret and uphold the shop's tradition as a coffee klatch for sharing local gossip, advice, and woes. But drama brews behind the counter, too. Grace is a single mother struggling with an unruly teenage daughter. Heartbroken Sarah has sworn off love. Macy's impending wedding has an unexpected hitch. And now charming developer Travis Butler has arrived in Devine with a checkbook and a handsome smile. He wants to buy the shop, expand it nationally, and boost the economy of a town divided by the prospect. With the family's relationships in flux, their beloved heritage up for grabs, and their future in the air, it's amazing what determination, sass, a promise of romance, and a warm maple doughnut can do to change hearts and minds."--